2018
DOI: 10.3389/fphar.2018.01184
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Rapamycin From FKBP Elastin-Like Polypeptides Is Consistent With Macropinocytosis

Abstract: Rapamycin (Rapa) is a highly potent drug; however, its clinical potential is limited by poor solubility, bioavailability, and cytotoxicity. To improve Rapa delivery, our team has fused the cognate protein receptor for Rapa, FKBP12, to high molecular weight elastin-like polypeptides (ELPs). One construct, FAF, includes an FKBP domain at each termini of an ELP. In a recent report, FAF/Rapa outperformed a family of related carriers with higher tumor accumulation and efficacy. Despite apparent efficacy, an explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…To support this contention, we recently reported that in vitro cellular uptake of FAF-Rapa occurs through macropinocytosis, which differed significantly from simple diffusion of free Rapa. 84 Further studies must now explore if FAF-Rapa exhibits a therapeutic effect at a subtherapeutic dose or frequency of free Rapa. These studies may solve the body weight loss (Table 3) and induction of hyperglycemia (Figure 8) observed during SC FAF-Rapa treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support this contention, we recently reported that in vitro cellular uptake of FAF-Rapa occurs through macropinocytosis, which differed significantly from simple diffusion of free Rapa. 84 Further studies must now explore if FAF-Rapa exhibits a therapeutic effect at a subtherapeutic dose or frequency of free Rapa. These studies may solve the body weight loss (Table 3) and induction of hyperglycemia (Figure 8) observed during SC FAF-Rapa treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If true, then it remains plausible that FAF–Rapa will remain associated even while interacting with lymphocytes and normal cells of the LG. To support this contention, we recently reported that in vitro cellular uptake of FAF–Rapa occurs through macropinocytosis, which differed significantly from simple diffusion of free Rapa . Further studies must now explore if FAF–Rapa exhibits a therapeutic effect at a subtherapeutic dose or frequency of free Rapa.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, macromolecule entry into cells is mainly mediated by cell surface receptors through different endocytic mechanisms, including clathrin-mediated endocytosis, clathrin-independent endocytosis (such as caveolae-mediated endocytosis), macropinocytosis, and phagocytosis. A well-documented example is the transferrin receptor, a dimeric carrier protein for transport of transferrin through clathrin-mediated endocytosis . Another example is the low-density lipoprotein receptor that binds cholesterol apolipoproteins and mediates the transport of LDL into cells through clathrin-dependent endocytosis .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that amiloride inhibited the delivery to the largest extent, by 42% as compared with the nontreated cells, while others did not display apparent inhibition activity, which suggested that the endocytosis of the protein-included FOFs by the cells occurred predominantly via the mechanism of macropinocytosis. 41,42 BSA, GFP, and OFP all bear a large number of hydrophobic side chains, and their isoelectric points are 4.7, 5.8, and 5.8, respectively. Thus, in the weakly alkaline media used for the intracellular…”
Section: ■ Introductionmentioning
confidence: 99%